Spondylodiscitis following sacral colpopexy procedure: is it an infection or graft rejection?. (November 2015) - Api, Murat; Kayatas, Semra; Boza, Aysen
Abstract: Spondylodiscitis is a rare but severe complication of sacral colpopexy (SC) procedure. Although the term 'spondylodiscitis' refers to infection of vertebral body and intervertebral disc space, neither the infecting microorganism could be isolated nor any purulent material could be observed during the second surgery and there was failure of different regimens of antibiotherapy. This type of spondylodiscitis cases might be explained by the graft rejection hypothesis. We hypothesize that the initiator of the rejection process is the host response solely and infection is just a co-incidence. In this situation, infection is neither a cause of this reaction, nor a promoter. There might be no infection at all. We presented two spondylodiscitis cases most probably secondary to graft rejection reaction and reviewed the literature in order to increase the awareness of this destructive complication of SC, which can only be ameliorated by surgical mesh removal.